Method to the madness of Chairman Kim: The instrumental rationality of North Korea's pursuit of nuclear weapons. (March 2014) - Cho, Youngwon
For two decades the Korean peninsula has been mired in a perilous nuclear brinkmanship with no end in sight. The paralysis is attributable in part to the widespread perception of North Korea as a "rogue" if not "mad" state, whose security concerns are seen as irrational, paranoiac, and illegitimate. Despite its eccentricities, however, Pyongyang is fundamentally a rational actor pursuing a rational strategy to deal with rational security concerns. Profound structural changes in the international system have rendered North Korea incapable of addressing its security anxiety through either internal balancing by conventional arms buildup or external balancing by alliance formation. In this context, nuclearization offers a logical and inexpensive route for Pyongyang to restore the military balance in the Korean peninsula and ensure its own survival.